A Textbook of Advanced Oral and Maxillofacial Surgery Volume 3 - Hosein Kalantar Motamedi, Mohammad (IntechOpen, 2016)
Advanced oral and maxillofacial surgery encompasses a vast array of diseases, disorders, defects, and deformities as well as injuries of the mouth, head, face, and jaws. It relates not only to treatment of impacted teeth, facial pain, misaligned jaws, facial trauma, oral cancers, jaw cysts, and tumors but also to facial cosmetic surgery and placement of dental and facial implants. This specialty is evolving alongside advancements in technology and instrumentation. Volume 1 has topped 132,000 chapter downloads so far, and Volume 2 is being downloaded at the same pace! Volume 3 is basically the sequel to Volumes 1 and 2; 93 specialists from nine countries contributed to 32 chapters providing comprehensive coverage of advanced topics in OMF surgery.